Natural Disaster Diversity Assessment of Bitlis Province - Rezzan Ekinci; Aydın Büyüksaraç; Yunus Levent Ekinci; Ercan Işık (Doğal Afetler ve Çevre Dergisi)
Bitlis province is located on a geography where natural disasters occur frequently due both to their geomorphologic structure and climatic features. However, necessary studies for disaster diversity inventory and consequently risk probability analyses have not been performed so far. In this study, temporal and spatial analyses of various natural disasters such as landslides, avalanches, rockfalls and floods occurred in Bitlis province were performed. Considering the damages resulted from the natural disaster occurrences, risk scores were calculated for the classifications. In order to perform risk analyses, the Fine-Kinney method, which is a method that uses the parameters of probability, severity and frequency, was employed. In this study, the method which is frequently used in occupational health safety studies was applied to risk analyses of natural disasters for the first time and therefore a new scale compatible with the aim of the study was determined and computations were made accordingly. It was decided that landslide, rockfall and avalanche events threaten the daily life in the districts which have sloped topographies and generally get heavy rainfall. Emergency actions that can be applied in case of a possible avalanche disaster are strongly recommended for Bitlis province that is most prone to be damaged by avalanche events. In addition, necessary precautions should be taken immediately to prevent the loss of life and property in the south districts, where the risk of rockfall events is high. On the other hand, it was determined that flooding events do not pose a serious danger.